Social media, expression, and online engagement: a psychological analysis of digital communication and the chilling effect in the UK - Daruwala, Neil Anthony (Frontiers in Communication, 2025)
IntroductionThe implementation of regulations such as the Online Safety Act by the United Kingdom government to combat hate speech and misinformation has raised critical questions about potential psychological and behavioral impacts on digital expression. This study explores how political orientation influences perceptions of online speech regulation and consequent self-censorship behaviors.MethodsAn online survey was conducted with 548 UK residents (ages 18–65+, M = 35.3), gathering demographic data (age, sex, political orientation). Participants completed the validated Chilling Effect Scale (Cronbach’s α ≥ 0.82), measuring willingness to speak openly online, self-censorship tendencies, and perceived fear of government penalties. Participants also evaluated two anonymised social media posts portraying contentious themes (supporting a terrorist organisation and advocating immigrant expulsion).ResultsParticipants showed higher self-censorship towards content perceived as potentially inciting harm. Political orientation significantly influenced willingness to speak out; specifically, “Very Liberal” participants were the most vocal, whereas Non-Political participants exhibited the highest self-censorship (F(5, 542) = 9.16, p < 0.001, η2 = 0.08). Additionally, liberal respondents were more sensitive to harmful content compared to conservatives or politically neutral individuals.DiscussionThe findings highlight the psychological effects of regulatory ambiguity, suggesting the necessity for clear regulatory definitions (e.g., specifying terms such as “legal but harmful”), transparent moderation policies, and support for cross-ideological dialogue. This research underscores critical factors for policymakers striving to balance public safety concerns with the preservation of free speech within polarized digital landscapes.